Who's who in Russia since 1900 - McCauley, Martin (Who's who series., 1997)
Who's Who in Russia since 1900is a unique reference guide which examines the leading political, economic, cultural, military, scientific and sporting personalities from 1900 to the present. Through analysis of figures such as Stalin, Brezhnev, Khrushchev, Yeltsin, Ratushinskaya and Sakharov, a comprehensive portrait of Russian and Soviet society in this era emerges. The book takes the reader up to the collapse of the Soviet Union and beyond. It provides: - detailed biographical information on each leading figure - bibliographical references with entries as an aid to further research - a comprehensive glossary of Russian terms, concepts and institutions and a useful chronology of events - an accessible and user-friendly A-Z layout - an invaluable guide for students, teachers, researchers, and the general reader alike.